On the metaphors in Codex Marianus from the cognitive point of view - Zábranský, Lukáš (Bohemica Olomucensia, 2013)
The author attempts to verify the methods of cognitive linguistics via analysis of metaphors found in the Gospel of Matthew of the Codex Marianus. The study examines the nature of the source domains of metaphorical concepts and presents possible partial conclusions. Within the individual domains the author takes into account etymology, anthropology and historical sociolinguistics.